2010
DOI: 10.1042/bj20100492
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nicotiana tabacum osmotic stress-activated protein kinase and its cellular partner GAPDH by nitric oxide in response to salinity

Abstract: Several studies focusing on elucidating the mechanism of NO (nitric oxide) signalling in plant cells have highlighted that its biological effects are partly mediated by protein kinases. The identity of these kinases and details of how NO modulates their activities, however, remain poorly investigated. In the present study, we have attempted to clarify the mechanisms underlying NO action in the regulation of NtOSAK (Nicotiana tabacum osmotic stress-activated protein kinase), a member of the SNF1 (sucrose non-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 65 publications
(103 reference statements)
2
82
0
2
Order By: Relevance
“…Although complex formation in the nucleus was not unaffected by stress conditions or NO donors, the interaction was abolished when both active-site cysteines of GAPDH were mutated into serines (Wawer et al, 2010). These studies were performed with Arabidopsis protoplasts expressing GAPDH under the control of the p35S promoter (Holtgrefe et al, 2008;Wawer et al, 2010), and in similar experiments, we could nicely confirm the nuclear localization of GAPC1-YFP expressed under the control of p35S (data not shown). However, replacing this constitutive strong promoter with the GAPC1 endogenous promoter largely prevented, in control conditions, the nuclear accumulation of GAPC1 (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Although complex formation in the nucleus was not unaffected by stress conditions or NO donors, the interaction was abolished when both active-site cysteines of GAPDH were mutated into serines (Wawer et al, 2010). These studies were performed with Arabidopsis protoplasts expressing GAPDH under the control of the p35S promoter (Holtgrefe et al, 2008;Wawer et al, 2010), and in similar experiments, we could nicely confirm the nuclear localization of GAPC1-YFP expressed under the control of p35S (data not shown). However, replacing this constitutive strong promoter with the GAPC1 endogenous promoter largely prevented, in control conditions, the nuclear accumulation of GAPC1 (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 67%
“…In animal cells, mechanisms independent on S-nitrosylation of catalytic Cys were also proposed for nuclear localization of GAPDH under several conditions (Sirover, 2011). Interestingly, Wawer et al (2010) also found that nuclear localization of the GAPDH-NtOSAK complex was not stimulated by NO donors, though complex formation did depend, somehow, on GAPDH catalytic Cys. Interestingly, in mammalian cells, several nonmetabolic functions have been reported for GAPDH in the nucleus, including posttranscriptional regulation and apoptosis (Sirover, 2011;Tristan et al, 2011).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…À ce jour, une cinquantaine de protéines S-nitrosylées a ainsi été identifiée, dont une dizaine ont fait l'objet d'études fonctionnelles approfondies (Tableau I). Il ressort de ces études que la S-nitrosylation module l'activité de ces protéines en ciblant directement des résidus Cys de sites actifs [24][25][26][27][28], en promouvant la formation de ponts disulfures [29,30], et en bloquant la fixation de cofacteurs (FAD ou ATP) par encombrement stérique [31,32]. Les données acquises pour les protéines NPR1 (nonexpressor of pathogenesis-related gene 1) et RBOHD (respiratory burst oxidase homologue D) sont détaillées ci-dessous à titre d'exemple (Figure 2).…”
Section: Identification Et Premières Analyses Fonctionnelles Des Protunclassified